Social Support among Mothers with Spouse Postpartum Depression - Nurhidayati, Evi; Dwiarini, Muafiqoh; Imamah, Nur Fithriyanti (Alta Dharma Publisher, 2024)
Introduction: Social support is one of the important things that affect factor for postpartum depression. Social support after childbirth is essential to reduce postpartum depression. Support from a spouse reduces psychological disorders among mothers. Objective: This study was to determine the social support among mothers with postpartum depression. Method: This study used a survey design. This research was conducted at Community Health Centers in Yogyakarta with 102 sample postpartum women. The study used the Edinburg Postpartum Depression Scale (EPDS), social support questionnaire, and demographic data questionnaires. The descriptive statistic uses percentage, mean, and standard deviation. Results: The results revealed that the mean score on the EPDS was 15.89 (SD ± 2.47). Generally, postpartum mothers showed moderate postpartum depression. Postpartum mother got high social support from their partner on average for the four subscales were respectively: emotional support 56.9%, household support 52%, babysitting support 51%, and help support 52.9%. Recommendation: Social support has an essential role in minimizing postpartum depression. Strategies to decrease postpartum depression should focus on increasing social support for postpartum mothers. The indicators of postpartum depression should be screened for and closely monitored by healthcare professionals. Additionally, healthcare professionals should provide sufficient assistance that is customized to the mother's needs through her spouse and family